Comparison of Postorthodontic Occlusal Force Distributions between Nonextraction and Extraction Treatment Approaches of Premolars for Orthodontic Treatment by Using T-Scan III System - Tansalarak, Ratchawan; Khamnuengsitthi, Nattapat; Pipatphatsakorn, Mayurach (European Journal of Dentistry, 2024)
Objective To compare bite force distributions in corresponding mouth regions between postorthodontic patients who underwent nonextraction and extraction approaches using the T-Scan III system (Tekscan, Inc, Massachusetts, United States).Materials and Methods Thirty-six postorthodontic patients were divided into two groups: (1) 18 subjects with the nonextraction treatment and (2) 18 subjects with the extraction of four first-premolar treatments. The measurements were performed using the T-Scan to collect the occlusal bite force at the maximal intercuspal position to generate the bite force in the anterior region (incisors and canines) and posterior region (premolars and molars), the bite force in individual teeth, and the anteroposterior bite force ratio (A-P ratio).Statistical Analysis The mean bite force in each region, individual teeth, and the A-P ratio were compared between the two groups by the Mann–Whitney's U-tests. Within-group comparisons of the mean bite force in each region were performed using Wilcoxon's signed rank tests.Results The bite force in anterior and posterior regions, and the A-P ratio of the nonextraction group show no significant difference compared with the extraction group (p > 0.05). For individual teeth (central incisors, lateral incisors, canines, second premolars, first molars, and second molars), each tooth exhibited nonsignificantly different bite forces (p > 0.05) except for the second molars. The second molars in the nonextraction group had significantly less bite force than in the extraction group (p = 0.001). The comparison of occlusal bite force between the right and left sides showed that in the nonextraction group, the right side had significantly greater force (p < 0.05). In the extraction group, there was no significant difference between the sides (p > 0.05).Conclusion Both nonextraction and extraction orthodontic treated patients exhibited the similar bite force distribution patterns in regions and individual teeth except for the higher occlusal force on the second molars in the extractions compared with the nonextractions.
Keywords: bite force; T-Scan III; tooth loss; postorthodontic; dental extraction